Development of a Web-Based School Budget Planning and Revenue Accounting Information System Using Agile Method - Delvia, Novita; Nugroho, Agus Cahyo; Koeswoyo, G. Freddy (Soegijapranata Catholic University, 2024)
Kanisius Foundation Branch Surakarta operates in the education field and covers 38 schools. The school's budget planning and revenue was drawn up at the beginning of the new academic year and reported using the Microsoft Excel application. Some schools have different data formats and structures, which cause data management is not well integrated. Based on these issues, the purpose of this research is to help the Kanisius Foundation Branch Surakarta by developing a School Budget Planning and Revenue Accounting Information System (RKAS), including billing and payment of school fees. This research uses agile methods. The first phase is planning, starting with an overview of RKAS revenue flows, student bills and payment flows. Then compile a Chart of Accounts (COA), create use case and create activity diagrams to design the database design and the basic framework of the program. Then the system is implemented using Laravel, followed by software testing with black box testing. Then the system documentation and deployment. The last stage is maintenance which is performed periodically at a certain time. The School Budget Planning and Revenue Accounting Information System will help Kanisius Foundation Branch Surakarta in management data and make accurate decisions through well-integrated data.